Respon Pertumbuhan Bibit Jabon (Anthocephalus Cadamba) Dengan Pemberian Kompos Kotoran Sapi Pada Media Penyapihan - Rekha Prananda; Indriyanto Indriyanto; Melya Riniarti (Jurnal Sylva Lestari, 2014)
Kadam is one type of fast growing trees species. One of the factors that affect plant growth are nutrients, the use of organic fertilizer such as cow manure compost soil mix additive during planting can increase nutrient substances in the soil that plants need for growth. The purpose of this experiment was to study the growth response of kadam seedling at different mixing ratio betwen soil with cow manure compost at seedling growth media and the best comparison of soil mixed with cow manure compost where gave the best effect on the growth of kadam seedling. The experiment was conducted from March until June 2012 in the nursery PT Subur Anugrah Sejahtera, District of Kaur, Sub District Air Palawan. The method used in this experiment was randomized block design (RBD) with 5 groups and 5 treatments.  Treatment of this experiment were growth media consisted of top soil, top soil + compost (1:1), top soil + compost (1:2), top soil + compost (1:3) and top soil + compost (1:4). Each experimental unit consisted of 10 seedlings. Similarity variety tested with Bartlett test, then performed analysis of variance and comparison of average values between treatments with HSD test, all the tests done at 5% significance level. The results showed that composition of soil and cow manure compost significantly affect to height, seedling height, dry weight of root, and seedling quality index. Composition of soil and cow manure compost 1:2 resulted the best of high growth, seedling high, dry weight of root, and the best seedling quality index respectively 42.64 cm, 40.56 cm, 10.22 g, and 8.73 g. For further research recommended to conduct the same study by replacing the type by cow manure compost white chiken manure compost as a growth media seedling so, can obtain new knowledge about the type of compost with for growth media. Keywords: compost, growth media, kadam